Symbiotic Interaction 5th International Workshop, Symbiotic 2016, Padua, Italy, September 29-30, 2016, Revised Selected Papers - Gamberini, Luciano; Spagnolli, Anna; Jacucci, Giulio; Blankertz, Benjamin; Freeman, Jonathan (Information Systems and Applications, incl. Internet/Web, and HCI, 2017)
This book is published open access under a CC BY license. This book constitutes the proceedings of the 5th International Workshop on Symbiotic Interaction, Symbiotic 2016, held in Padua, Italy, in October 2016. The 12 full papers and 3 short papers presented in this volume were carefully reviewed and selected from 23 submissions. The idea of symbiotic systems put forward in this workshop capitalizes on the computers' ability to implicitly detect the users goals, preferences or/and psycho-physiological states and thereby enhancing human-computer interaction (HCI). The papers present an overview of the symbiotic relationships between humans and computers with emphasis on user-driven research on symbiotic systems, adaptive systems, implicit input data, physiological computing and BCI, but also on understanding the nature of the interdependence and agency between computers and humans more broadly.